The Effect Of Capital Structure And Company Size On Company Value With Profitability As Moderating Variables - Maria Yasinta Deme; Sunardi Sunardi; Sari Yuniarti (Eduvest - Journal of Universal Studies, 2022)
The purpose of this study was to analyze the effect of capital structure and firm size on firm value with profitability as a moderating variable. This study is a quantitative study using secondary data with a sample of 9 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX). The data collection method is done by accessing the company's financial statements published by the Indonesia Stock Exchange. The data obtained is then processed using the tools e-views. This analysis includes classical assumption test (data normality test, multicollinearity test and heteroscedasticity test), statistical test (F-test, t-test and R2 test) and moderated regression analysis (MRA). Based on the results of the tests conducted, it shows that simultaneously shows that there is a significant influence between capital structure and firm size on firm value. Partially, Capital Structure (DER) has a significant effect on firm value (EPS), Firm Size (SIZE) has no significant effect on firm value, Profitability (ROA) as a moderating variable can moderate or strengthen the relationship between Capital Structure (DER) and Firm Value ( EPS) but unable to moderate the effect of Firm Size (SIZE) on Firm Value (EPS).